PHYSIOTHERAPY MANAGEMENT FOR PATIENT WITH PRIMARY SPONTANEOUS PNEUMOTHORAX DEXTRA: A CASE STUDY - Listyana, Lifia Rahma; Sudaryanto, Wahyu Tri; Haris, Abdul (Academic Physiotherapy Conference Proceeding, 2021)
Introduction : Primary Spontaneous Pneumothorax is the presence of air or gas in the pleural cavity that can cause the lung to collapse but without any prior chest trauma or history of lung disease. Generally, patients with primary spontaneous pneumothorax present with chest pain accompanied by breathless to decreased thoracic expansion. The purpose of this case study is to report the results of a physiotherapy program in a patient with primary spontaneous pneumothorax. Case Presentation : The patient was a 62-year-old male laborer, was diagnosed with primary spontaneous pneumothorax dextra. The patient reported the breathless with non-productive cough. Asymmetrical chest movements, with the dextra lower than the sinitra. Chest X-ray showed that dextra lung had collapse. Management and Outcome : The intervention was given one session every day for 7 days consist of Segmental Breathing Exercise, Thoracic Expansion Exercise, and Pursed Lip Breathing. Each program is repeated 3-5 times, interspersed with rest and Breathing Control. Evaluation of the results of the intervention in measuring the degree of breathless using the Brog Scale, measuring thoracic expansion using a medline, as well as the results of a chest X-ray. Discussion : The physiotherapy program in cases of primary spontaneous pneumothorax is given segmental breathing exercise and thoracic expansion exercise to increase thoracic expansion and maximize the inspiration-expiration process. The pursed lip breathing program aims to relieve breathless interspersed with breathing control to restore a calm breathing pattern. Conclusion : Physiotherapy management for patient withprimary spontaneous pneumothorax dextra with the intervention that is Segmental Breathing Exercise, Thoracic Expansion Exercise, Pursed Lip Breathing can relieve breathless, increase thoracic expansion and restore lung function.